Magnetic Supported Copper Nanoparticles: An Efficient Heterogeneous Catalyst for the Synthesis of 1, 2‐Diketones by Cross‐Coupling Reaction of Imidazo[1, 2‐a]pyridines with Methyl Ketones. Issue 29 (21st September 2016) - Liu, Yi; Zhan, Haiying; Yao, Kefan; Mai, Yingying; Wang, Enmin; He, Juan; Guo, Pengfeng
Abstract : A convenient and new copper nanoparticles‐catalyzed cross‐coupling reaction of imidazo[1, 2‐ a ]pyridines with methyl ketones has been developed to synthesize 1, 2‐diketones that have an imidazo[1, 2‐ a ]pyridine core. Highly active magnetic copper nanoparticles [i.e., Cu4 O3 @Fe3 O4 _C(II)] were prepared and characterized by standard materials characterization techniques, which included transmission electron microscopy, scanning electron microscopy, X‐ray photoelectron spectroscopy (XPS) and X‐ray diffraction. These methods were also used to acquire information about the size, oxidation state, and crystallinity of the nanoparticle catalyst. With this method, a variety of pharmaceutically important 1, 2‐dicarbonyl imidazo[1, 2‐ a ]pyridines were readily synthesized in moderate to good yields. The catalyst was easily separated from the reaction mixture by using an external magnetic field and could be recycled 6 times with only a negligible change in the catalytic performance. Abstract : A nanoparticles‐catalyzed cross‐coupling reaction of imidazo[1, 2‐ a ]pyridines with methyl ketones was developed. The Cu4 O3 @Fe3 O4 _C(II) catalyst was synthesized, characterized, and used for the synthesis of 1, 2‐dicarbonyl imidazo[1, 2‐ a ]pyridines. This copper catalyst can be easily separated from the reaction mixture and recycled up to six times without any significant loss of activity.